2014
DOI: 10.4103/0976-7800.133989
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal symptoms of postmenopausal women in a rural community of Delhi, India: A cross-sectional study

Abstract: Background:There is very little data on the consequence of menopause on women in South East Asia region, especially from rural India. Importance is always given to reproductive health from menarche to menopause. Menopausal health demands priority in Indian scenario due to rising population of postmenopausal women.Objectives:The aim was to determine the mean age at attaining menopause and the prevalence of various self-reported menopausal symptoms complained by postmenopausal women (40-54 years). Furthermore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
61
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 10 publications
10
61
2
3
Order By: Relevance
“…In the study by Akansha et al, it was 89.3% and that by Alakananda et al, it was 80.5 % which is almost similar to the present study. 2,4 Hot flushes were the most common symptoms with 58% suffering from it while 42% had excessive sweating. In the study by Alakananda et al, it was 52.5% and 48.5% respectively which is comparable with this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Akansha et al, it was 89.3% and that by Alakananda et al, it was 80.5 % which is almost similar to the present study. 2,4 Hot flushes were the most common symptoms with 58% suffering from it while 42% had excessive sweating. In the study by Alakananda et al, it was 52.5% and 48.5% respectively which is comparable with this study.…”
Section: Discussionmentioning
confidence: 99%
“…15 Compared to the Western World, the prevalence of osteopenia and osteoporosis is much higher in our and other Indian studies, reflecting poor overall health of menopausal women and women in general in India. 6,8 The prevalence of low BMD (osteopenia and osteoporosis) is 77% in our study (50.5% with osteopenia and 26.5% with osteoporosis).…”
mentioning
confidence: 47%
“…6 Across the world, there is a considerable variation among women regarding the age of attaining menopause and the manifestation of menopausal signs and symptoms. 7 In 1990, about 25 million women worldwide reached menopause; this number is expected to double by the late 2020s.…”
Section: Discussionmentioning
confidence: 99%
“…The 3 most common problems that cause discomfort to women during the postmenopausal period are vasomotor changes, insomnia, and fatigue (Ameratunga, Goldin, & Hickey, 2012;Lai, Chen, Chen, Chen, & Wang, 2006;Timur & Şahin, 2010;Timur & Şahin, 2012). The incidence of insomnia during the menopausal period ranges between 12% and 70% in the literature (Perez, Garcia, Palacios, & Perez, 2009;Simon & Reape, 2009;Singh & Pradhan, 2014;Taavoni, Ekbatani, Kashaniyan, & Haghani, 2011;Terauchi et al, 2010). Perez et al (2009) found that the postmenopausal period has the highest insomnia rate of all periods in human life (49.4%) (Perez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%